The Urgency of Providing Health Infrastructure in Improving the Quality of Life and Creating a Golden Generation in 2045 in Villages - Kalalo, Rieneke Ryke; Simatupang , Septian; Simatupang , Mumu Muzayyin Maq; Muktar , Muktar; Arif , Muhammad (Journal Of Human And Education (JAHE), 2024)
One of the most important components in realizing health development in realizing the 2045 golden generation in Indonesia is the availability of health infrastructure. Therefore, the Ministry of Health is disbursing a health welfare budget of 5% of the APBN and APBD to cities and districts, which is expected to play a role in helping improve health infrastructure and superstructure for the community, especially communities in villages where the development and provision of health facilities is not evenly distributed. As for appropriate and targeted health infrastructure, village communities can influence the implementation of health programs in the village. Uneven implementation of health infrastructure can cause difficulties for individuals to reach the necessary health facilities. Therefore, the aim of this community service is to determine the urgency of the influence of providing health infrastructure in improving the quality of life and health of people in villages so that they can create the 2045 Golden Generation in Indonesian. In obtaining the data used were observation and literature review. This service activity is an educational and outreach effort to the people of Garung Village, Sambeng District, Lamongan Regency, East Java. This effort was motivated by the lack of knowledge about the provision of health infrastructure in villages which is very useful for improving the quality of life and health of the community. As a form of the author's thinking, several efforts and breakthroughs are offered, namely; 1.) Accessibility of Health Service Infrastructure, availability of medical personnel, supporting facilities, quality of service, and regional disparities are factors that influence the provision of health infrastructure in villages. 2.) Knowledge, community views, education and health infrastructure are factors that can influence village communities in obtaining information to improve the quality of life and health of the community so that they can create the 2045 golden generation Indonesian generation.